Characterization and classification of soils of selected watershed area of Haryana, North-west India - SAHOO, JYOTIRMAYA; DINESH, DINESH; BHAT, MOHAMMAD AMIN; ANIL, AJIN S; ANURAG, ANURAG (The Indian Journal of Agricultural Sciences, 2019)
In the present study, undertaken in 2017–18 at CCS Haryana Agricultural University, eight typical pedons representing micro watersheds, viz. Motipura (P1 and P2), Sainiwas (P3 and P4), Jhumpa (P5 and P6), Budhsheli (P7 and P8), in semi-arid ecosystem of Jhumpa Kalan watershed of Bhiwani district of Haryana, were studied for morpho-physical, chemical characteristics and their classification. Results indicated that soils of micro watershed pedons varied in colour from dark brown to dark yellowish brown with sand to loamy sand texture along with higher sand content as compared to silt and clay. These soils were slightly to moderately alkaline in reaction and non-saline. The bulk density, available water content, organic carbon (OC), cation exchange capacity (CEC) and base saturation varied from 1.38 to 1.62 Mg/ m3, 2.04 to 13.78%, 0.06 to 0.27%, 2.21 to 7.85 cmol (p+)/kg and 88.36 to 98.57% respectively. Due to the presence of ustic/arid soil moisture regime, hyperthermic temperature regime and low organic matter content, the soils were classified into Typic Torripsamments (P4 and P8)/ Ustipsamments (P1, P2 and P3) and Typic Calciorchids (P7)/ Cambiorchids (P5).